An Overview of Competency Management for Learning and Performance Support: A Canadian Perspective - Kondratova, Irina; Fourier, Helene; Molyneaux, Heather (International Journal of Advanced Corporate Learning (iJAC), 2017)
Despite the turbulent economy, recent expenditures on workplace learning in North America have increased. Technology-based methods including tools that enable social learning are making significant gains and account for 39% of all training hours in 2012. A majority of companies are moving from static classroom training to workplace learning that is more interactive and driven by technology. Companies actively experiment with new methods such as personalized learning, performance support, and gamification to encourage employees’ motivation to learn and promote continuous workplace learning, practice and application. However, the divide between the training and competencies people have and the training and competencies companies need still remains. The National Research Council Canada (NRC)’s Learning and Performance Support Systems (LPSS) program, by implementing adaptive and personalization strategies, develops software components for learning, training, performance support and enterprise workforce optimization. These technologies have the potential to facilitate lifelong learning, reduce learning and training costs, and reduce demands on physical infrastructure. Software components being developed for learning, training and performance support also enable streamlined and rapid skill development, as well as reduce time to competency, support informal, personal and personalized learning, increase learner engagement, address workforce optimization and sustainability, and increase operational performance and productivity. An overview of the LPSS system and capabilities is presented along with the results of our review of the current state of competency management in Canada and some challenges in this area, followed by recommendations for further work on competency functionality in the context of the LPSS program.